Influence of different polyethylene wax additives on the performance of modified asphalt binders and mixtures. (4th October 2021) - Zhang, Yu; Song, Qingqing; Lv, Quan; Wang, Hongxin
Highlights: Three types of PW additives with different Mw were compared in this paper. A good correlation was found between Mw and the modified effects of PW additives. The moisture susceptibility of PW modified mix was evaluated by a new parameter SSR. OPW showed the best modifying performance due to its uniform microstructure. Abstract: This study aims at investigating the influence of polyethylene wax (PW) additives on the performance of modified asphalt binders and mixtures. Three types of PW additives, including low density wax (LDPW), high density wax (HDPW), and oxidized polyethylene wax (OPW) were selected with different molecular weight (Mw ). Fischer-Tropsch wax (FTW) and Montan wax (MW) additives were also selected for comparison. Then, several laboratory tests were conducted, including performance grade test, storage ability test, viscosity test, workability test, wheel tracking test, Hamburg wheel tracking device test (HWTD), tensile strength ratio (TSR) test, bending beam test and semi-circular bending (SCB) test. Besides, the fluorescence microscopy test was conducted to investigate the modifying mechanism of different wax additives. Results indicate that, almost all tested wax additives improve the high temperature stability and moisture resistance capacity of the asphalt mixture, while reduce the low temperature stability. As the Mw increases, the rational viscosity of the asphalt binder, the moisture resistance capacity and low temperature stability of PW modified asphalt mixture increases, while the storage stability decreases. PW additives perform better in low temperature cracking resistance capacity than AMW and FTW. OPW has the best modifying performance among all selected PW additives due to the uniform microstructure.